Peran Auditor Eksternal dalam Menjaga Kepatuhan dan Transparansi Laporan Keuangan Pada Perusahaan - Arya Saputra; Desilvia; Masyhuri, Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the strategic role of external auditors in strengthening corporate compliance and transparency in financial reporting. In an increasingly complex business environment, companies are required to present financial statements that are reliable, accurate, and free from manipulation. As independent examiners, external auditors provide objective assurance regarding the fairness of financial information and help reduce information asymmetry between management and stakeholders. This research employs a literature review method by analyzing academic publications, accredited journals, and regulatory data to understand the contribution of external auditing to corporate accountability. The findings indicate that high-quality external audits enhance compliance with accounting standards, improve the disclosure of material information, and support companies in strengthening their internal control systems. Data from the Financial Services Authority (OJK) also show an increase in reporting violations, highlighting the urgent need for stronger independent oversight. External auditors play a critical role in detecting irregularities, preventing fraudulent practices, and ensuring that financial statements accurately reflect a company’s economic condition. The study concludes that external auditors are a vital component of modern corporate governance, as they reinforce reporting credibility and bolster public and investor trust.